2010
DOI: 10.1590/s0104-11692010000700016
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de drogas en los jóvenes de la ciudad de Guayaquil, Ecuador

Abstract: El objetivo de esta investigación fue conocer las causas predominantes y el tipo de droga que más consumen los jóvenes de 10 a 18 años que ingresaron en una institución que acoge niños infractores de una ciudad del Ecuador. Se trata de un estudio descriptivo y cualitativo, cuya recolección de datos ocurrió mediante entrevista semiestructurada e individual. Participaron diez jóvenes, con edades entre 10 y 16 años. El análisis de contenido resultó en tres temas: la carencia del apoyo familiar; las influencias de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…Studies carried out with a student population have shown that peer pressure, as well as the pressure and influence of media regarding psychoactive drugs, represented by alcohol and tobacco, are risk factors that favor simultaneous use. [29][30][31] Previous studies with the university population in El Salvador have shown similar results in regard to the influence of peers as a risk factor for drug consumption. 13,22 The drugs most used by friends over the last 12 months were alcohol, tobacco, and cannabis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Studies carried out with a student population have shown that peer pressure, as well as the pressure and influence of media regarding psychoactive drugs, represented by alcohol and tobacco, are risk factors that favor simultaneous use. [29][30][31] Previous studies with the university population in El Salvador have shown similar results in regard to the influence of peers as a risk factor for drug consumption. 13,22 The drugs most used by friends over the last 12 months were alcohol, tobacco, and cannabis.…”
Section: Discussionsupporting
confidence: 60%
“…The most used drugs over the last 12 months were alcohol, cannabis, and tobacco, with a prevalence of 14% (38), 9.3% (26), and 7% (19) respectively. The most used drugs over the last 30 days were alcohol, tobacco, and cannabis, with a prevalence of 16.9% (46), 11.0% (30), and 4.4% (12) respectively. The least used drugs over the last 12-month and 30-day periods were heroin and inhalants, respectively.…”
Section: Use Of Psychoactive Drugsmentioning
confidence: 99%
“…In our study, there was a higher prevalence of consummation in adolescents who always have their privacy invaded by parents, but this association was significant among males, not among females. The adolescents have reported, among other factors, that the lack of structure and family support are some of the reasons why they have started using illicit drugs 22,23 . On the other hand, several other factors of family protection to prevent drug use are mentioned in studies, such as demonstrations of affection toward children, easy communication, adequate flexibility in the creation and application of rules 6,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Últimos aportes investigativos han defino varias causas de consumo de drogas en adolescentes de Ecuador como son: la carencia del apoyo familiar, las influencias en que se desarrollan los jóvenes, el desconocimiento que causan las drogas y planes para el futuro (Riofrío G & Nascimento, 2010), la permisibilidad legal y despenalización (Loor et al, 2018). También, Ramírez & de Andrade (2005) mencionan como causas para el consumo de alcohol y tabaco: el factor económico, la baja escolaridad, padre bebedor, nivel de escolaridad, y la edad .…”
Section: Síntomas De Ansiedad Y Depresión Asociadosunclassified